Deciphering the finest imprint of glacial erosion: objective analysis of striae patterns on bedrock - Stroeven, Piet (Image analysis and stereology, 2005)
The aim of this study is to compare the efficiency of different mathematical and statistical geometrical methods applied to characterise the orientation distribution of striae on bedrock for deciphering the finest imprint of glacial erosion. The involved methods include automatic image analysis techniques of Fast Fourier Transform (FFT), and the experimental investigations by means of Saltikov's directed secants analysis (rose of intersection densities), applied to digital and analogue images of the striae pattern, respectively. In addition, the experimental data were compared with the modelling results made on the basis of Underwood's concept of linear systems in a plane. The experimental and modelling approaches in the frameworkof stereology yield consistent results. These results reveal that stereological methods allow a reliable and efficient delineation of different families of glacial striae from a complex record imprinted in bedrock.
Keywords: Fourierjeva analiza; Materials Testing; Image Processing, Computer-Assisted; Materiali, testiranje; Fourier Analysis; Slika, obdelava z računalnikom; preiskava materiala; erozija; stereologija; metode; Fourierjeva transformacija